2022
DOI: 10.3390/antiox11112268
|View full text |Cite
|
Sign up to set email alerts
|

ANTIAGE-DB: A Database and Server for the Prediction of Anti-Aging Compounds Targeting Elastase, Hyaluronidase, and Tyrosinase

Abstract: Natural products bear a multivariate biochemical profile with antioxidant, anti-inflammatory, antibacterial, and antitumoral properties. Along with their natural sources, they have been widely used both as anti-aging and anti-melanogenic agents due to their effective contribution in the elimination of reactive oxygen species (ROS) caused by oxidative stress. Their anti-aging activity is mainly related to their capacity of inhibiting enzymes like Human Neutrophil Elastase (HNE), Hyaluronidase (Hyal) and Tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 187 publications
(255 reference statements)
0
7
0
2
Order By: Relevance
“…28 Among the identified compounds, free fatty acids were also previously reported to exhibit collagenase and elastase inhibitory activities. 108,109…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Among the identified compounds, free fatty acids were also previously reported to exhibit collagenase and elastase inhibitory activities. 108,109…”
Section: Discussionmentioning
confidence: 99%
“…28 Among the identified compounds, free fatty acids were also previously reported to exhibit collagenase and elastase inhibitory activities. 108,109 Indicaxanthin was previously reported in OFI peel and pulp, besides other betalain compounds. 82,110,111 In our study, indicaxanthin was the only betalain compound identified.…”
Section: Food and Function Papermentioning
confidence: 96%
“…Early in 2019, Wang et al proved that 200 μg/mL ethanol extracts of I. obliquus showed the best antiaging effect in PC12 cell models among other test samples [ 236 ]. After using S. vaninii methanol and hot water extracts in vitro that mainly contain phenolic and flavonoid components, Li et al reported an antiwrinkle ability based on the inhibiting effect on tyrosinase, the self-oxidation of L-3,4-dihydroxyphenylalanine (L-DOPA), elastase, and collagenase; these are critical molecules in the body and arterial aging [ 162 , 237 , 238 ]. Also, in 2019, Gu et al stated that a Sanghuang decoction consisting of 2 g/mL crude medicine, mostly polysaccharides, triterpenoids, and flavonoids, could initiate the transcription of gene HO-1, thereby inhibiting oxidative stress and delaying the progression of aging [ 181 ].…”
Section: Health-improving Effectsmentioning
confidence: 99%
“…Antioxidant Activity Antioxidants are chemicals that limit or stop cell oxidation caused by free radicals. [35]. To keep the body functioning at its best, antioxidant supplementation is a growingly common practice [36].…”
Section: Black Pepper Extractmentioning
confidence: 99%
“…Free radicals can harm cells, resulting in early aging and several disorders. One effort to capture free radicals is antioxidants such as vitamins C and E ( [35].…”
Section: Black Pepper Extractmentioning
confidence: 99%